2021
DOI: 10.1016/j.jbc.2021.101018
|View full text |Cite
|
Sign up to set email alerts
|

Binding of a pyrimidine RNA base-mimic to SARS-CoV-2 nonstructural protein 9

Abstract: The coronaviral non-structural protein 9 (Nsp9) is essential for viral replication; it is the primary substrate of Nsp12’s pseudokinase domain within the viral replication transcription complex, an association that also recruits other components during different stages of RNA reproduction. In the unmodified state, Nsp9 forms an obligate homodimer via an essential GxxxG protein-interaction motif, but its ssRNA-binding mechanism remains unknown. Using structural biological techniques, here we show that a base-mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 37 publications
0
13
0
Order By: Relevance
“…A previous study identified the possible RNA-binding sites (Phe40, Val41, and Ile91) by observing the chemical perturbation of Nsp9 titrated with ssRNA using nuclear magnetic resonance (NMR) titration assays. 216 Subsequently, targeted substrates that bind to these sites (or adjacent to these sites) were screened from a small fragment library; the uracil-analog FR6, which has a weak affinity with Nsp9, was obtained. 216 In the Nsp9/FR6 complex, a tetrameric π–π stacking between the pyrimidinedione ring of FR6 and the aromatic ring of Phe40 induces a hexameric form of Nsp9 (a “trimer of dimers”).…”
Section: Nonstructural Proteins Of Sras-cov-2mentioning
confidence: 99%
See 2 more Smart Citations
“…A previous study identified the possible RNA-binding sites (Phe40, Val41, and Ile91) by observing the chemical perturbation of Nsp9 titrated with ssRNA using nuclear magnetic resonance (NMR) titration assays. 216 Subsequently, targeted substrates that bind to these sites (or adjacent to these sites) were screened from a small fragment library; the uracil-analog FR6, which has a weak affinity with Nsp9, was obtained. 216 In the Nsp9/FR6 complex, a tetrameric π–π stacking between the pyrimidinedione ring of FR6 and the aromatic ring of Phe40 induces a hexameric form of Nsp9 (a “trimer of dimers”).…”
Section: Nonstructural Proteins Of Sras-cov-2mentioning
confidence: 99%
“… 216 Subsequently, targeted substrates that bind to these sites (or adjacent to these sites) were screened from a small fragment library; the uracil-analog FR6, which has a weak affinity with Nsp9, was obtained. 216 In the Nsp9/FR6 complex, a tetrameric π–π stacking between the pyrimidinedione ring of FR6 and the aromatic ring of Phe40 induces a hexameric form of Nsp9 (a “trimer of dimers”). 216 Changes in the oligomerization state may alter RNA entry channels and thus affect RNA binding.…”
Section: Nonstructural Proteins Of Sras-cov-2mentioning
confidence: 99%
See 1 more Smart Citation
“…Although NiRAN has no homologs in other RNA viruses, it is present in all nidoviruses and is essential for viral replication [34]. The NiRAN domain is structurally homologous to AM-Pylases [35,36], which catalyze AMP transfer to target proteins [37], and transfers NMPs to several nsps [19][20][21]38]. In contrast to AMPylases, which transfer AMP to hydroxyl groups of Ser, Thr, and Tyr residues to generate stable modifications [37], the NiRAN active site (AS2 in Figure 1) targets primary amines to yield labile adducts [19], which are used as transient catalytic intermediates in other enzymatic systems [39].…”
Section: Sars-cov-2 Niran Domain As a Target For Small-molecule Ligandsmentioning
confidence: 99%
“…The 12 kDa nonstructural protein 9 (Nsp9) forms a homodimer that functions as an essential RNA binding subunit of the replication complex (de et al, 2021 ). Because disruption of Nsp9 binding to the replication complex reduces RNA binding and SARS‐CoV proliferation, ligands to Nsp9 are potential anti‐SARS‐CoV‐2 agents (Littler, Mohanty, et al, 2021 ). Native MS screening has been used to discover Nsp9 ligands that can inhibit the replication of SARS‐CoV‐2 (Littler, Liu, et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%